Immunotoxic effects of in vitro exposure of dolphin lymphocytes to Louisiana sweet crude oil and Corexit™. Issue 6 (20th November 2016) - White, Natasha D.; Godard‐Codding, Celine; Webb, Sarah J.; Bossart, Gregory D.; Fair, Patricia A.
Abstract: The Deepwater Horizon oil spill was one of the worst environmental disasters on record in the United States. Response efforts to reduce the magnitude of the oil slick included the use of thousands of gallons of the chemical dispersant Corexit™ in surface and deep‐water environments. The immunotoxicity of Louisiana sweet crude oil and the chemical dispersant Corexit was examined using lymphocyte proliferation (LP) and natural killer cell (NK) assays as measures of impact on the adaptive (LP) and innate (NK) immune response in bottlenose dolphins. Study results show that both high‐energy media‐accommodated fractions (MAF) and chemically enhanced MAF (CEMAF) mixtures modulate immune function. Following exposure to Louisiana sweet crude, both B‐ and T‐cell proliferation of white blood cells was increased for all exposure concentrations, compared to control; however, this increase was only significant for the 50% and 100% treatments. In contrast, exposure of white blood cells to the CEMAF mixture significantly decreased both T‐ and B‐cell proliferation in the 25%, 50% and 100% treatments. NK cell activity was enhanced significantly by CEMAF mixtures for the 50% and 100% treatments. The immunosuppression of LP at environmentally relevant concentrations of oil and dispersant suggests that marine mammals may be unable to mount an adequate defense against xenobiotic threats following exposure to oil and dispersant, leaving them more susceptible to disease. In contrast, NK cell activity was significantly enhanced, which may increase an organism's tumor or viral surveillance ability by mounting an enhanced immune response. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The immunotoxicity of Louisiana sweet crude oil and the chemical dispersant Corexit™ was examined using lymphocyte proliferation and natural killer cell assays as measures of impact on the adaptive and innate immune response in bottlenose dolphins, respectively. Bottlenose dolphin peripheral blood leukocytes were exposed to Louisiana sweet crude alone and in combination with Corexit. Results observed in this study indicate that exposure to both oil and dispersants causes functional impairment of cells of both the innate and adaptive immune system of bottlenose dolphins at environmentally relevant concentrations.